2020
DOI: 10.1136/jech-2020-213946
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the educational gradient in allostatic load across European populations. What matters the most: differentials in exposure or in susceptibility?

Abstract: BackgroundWe investigate whether socially disadvantaged individuals are more susceptible to the detrimental effects of smoking and alcohol intake on allostatic load (AL), a marker of physiological ‘wear and tear’, resulting from adaptation to chronic stress.MethodsIn a cross-sectional analysis, 27 019 men and 26 738 women aged 35–74 years were identified from 21 European cohorts in the BiomarCaRE consortium. We defined three educational classes (EDs) according to years of schooling and an AL score as the sum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Our findings therefore align with long established linkages between income and health and well-being (27)(28)(29)(30), and also with continued contemporary trends in self-reported health across Europe surrounding income (18,19) and in North America surrounding education (16,31). In addition, our findings support empirically derived evidence indicating the significant impact education (32) and income (17, 33) have on general health. However, the work of Sinha et al (34) indicates that there are potentially better indicators of poor health than income, and that tackling persistent deprivation in dimensions such as housing conditions and social isolation may be more fruitful.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings therefore align with long established linkages between income and health and well-being (27)(28)(29)(30), and also with continued contemporary trends in self-reported health across Europe surrounding income (18,19) and in North America surrounding education (16,31). In addition, our findings support empirically derived evidence indicating the significant impact education (32) and income (17, 33) have on general health. However, the work of Sinha et al (34) indicates that there are potentially better indicators of poor health than income, and that tackling persistent deprivation in dimensions such as housing conditions and social isolation may be more fruitful.…”
Section: Discussionsupporting
confidence: 87%
“…In this prospective cohort study, we found evidence for the effect of differential exposure to AL on CHD incidence. As differential susceptibility in men was found in our companion paper to have a predominant role in the accumulation of AL in low educational classes, 14 further investigation of AL-related risk factors is needed. Meanwhile, any preventive action aiming to control factors linked to the disproportionate exposure to excess AL may help to reduce CHD morbidity, in particular among those with lower education.…”
Section: Discussionmentioning
confidence: 78%
“…In the same populations, we previously found that the educational gradient in AL in men was largely attributable to differential susceptibility to behavioural factors. 14 In particular, being a never smoker or having moderate alcohol intake was less protective in terms of AL accumulation in less educated men compared with their more educated counterparts. In women, the educational gradient in AL remained largely unexplained by both differential exposure and susceptibility to the same behavioural factors.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation